Metodología para la construcción de la base de conocimiento de un sistema experto - Méndez Giraldo, Germán Andrés; Álvarez Pomar, Lindsay (Ingeniería, 2002)
In the past the knowledge acquisition and its transferring at expert system were the most important bottleneck to develop this decision tool. Now, knowledge engineering is improving its applications to develop better methodologies and other tools to transfer of the expert to system. This paper presents a new methodology to acquire knowledge in order to do a Diagnostic PyMes with Expert System. This methodology is based on interactive tools used in the industry; these include tools for extracting knowledge, joining analysis useful in design rapid prototypes. By the way include tools for dynamic analysis using continuous simulation, it offers complementary approximation to acquire expert knowledge.